A Synoptic Ecopath model of biomass flows during two different static ecological situations in Lake Nakuru (Kenya) - Moreau, Jacques; Mavuti, Kenneth; Daufresne, Tanguy (Department of Zoology, University of Nairobi, 2001)
Trophic relationships inside the Lake Nakuru ecosystem during two different phases are described by using the ECOPATH model. This allows a partial explanation of the ecological changes observed in the lake and to show that this apparently unstable ecosystem is characterized by constant transfer efficiencies within the existing trophic levels.
Keywords: Modelling ecological evolutions; Trophic status